(untitled) (CIPEEX, 2026)
Triazole fungicides, widely used in agriculture to control plant pathogens, pose potential risks to human health due to their ability to interfere with metabolic pathways conserved between fungi and mammals. This study aims to review the toxic effects associated with human exposure to agricultural triazoles, highlighting the most frequently affected target organs. The methodology consisted of a narrative review of scientific articles indexed in PubMed, SciELO, and Google Scholar, including experimental toxicology, epidemiology, and fungal resistance analyses. The results showed that, in addition to environmental and soil microbiota impacts, triazoles can induce cross-resistance in Aspergillus fumigatus, compromising the efficacy of clinical antifungals, and causing endocrine effects, hepatotoxicity, and neurological alterations in humans. It is concluded that the intensification of agricultural use of triazoles constitutes an emerging concern for public health, requiring more rigorous regulatory monitoring, risk mitigation strategies and encouragement of sustainable alternatives.